The Lived Experiences and Perceptions of Social Studies Teachers and School Administrators on the Out-Of-Field Teaching Phenomenon in Zamboanga City - Toring, Sherwin (JPAIR Multidisciplinary Research, 2017)
This study sleuthed on the wide yet less explored issue called out-of-field teaching among the public junior high schools in Zamboanga City, Philippines. It focused on the extent and experiences of teachers who are assigned to teach social studies but are not licensed in it and conversely those licensed but are assigned to teach outside the field of social studies. It also sought to discuss the perceptions of some school administrators on the factors that lead to the occurrence of the phenomenon. Data were mainly gathered using a descriptive-qualitative method, particularly through survey, interviews, and document analysis. The results revealed that 37% of the teachers assigned to teach social studies is teaching out of their field of specialization. Interviews also show a consensus in identifying under-loading of teachers, lack of resources, and the lack of coordination between the HEIs and DepEd as main factors to out-of-field teaching in the city. It also suggests that out-of-field teachers experience a certain degree of emotional and physical stress and difficulty in understanding certain contents and practical concepts. These are reflected on their instructional practices that include the reliance on textbooks and the use of survival strategies such as lectures, group reports, and video presentations. This situation can be partly attributed to and/or is further exacerbated by onerous number of subject preparations and the unavailability of adequate instructional resources.